Observational Study Implementation of STEAM Activities to Stimulate 21st Century Skills in Early Childhood - Prastyaningrum, Ihtiari; Alfina, Alisa; Shella, Geo (Yayasan Indonesia Emerging Literacy Education, 2025)
Learning with the STEAM approach has begun to be implemented in early childhood education settings. The STEAM approach provides significant opportunities to stimulate students’ critical thinking skills. This phenomenon requires teachers to have a deep understanding of STEAM. Therefore, research is needed to reveal the extent to which STEAM activities are implemented in the classroom and how teachers are able to manage the learning environment to be more conducive in relation to the implementation of STEAM activities. This observational study aims to determine and analyze the extent to which teachers in early childhood education are able to carry out learning activities using the STEAM approach. It also aims to analyze how teachers are able to stimulate 21st-century skills through the implementation of the STEAM approach. The research data were collected through two main activities, namely observation and interviews. Observation and interviews were considered the most effective steps in gathering research data. The data obtained were analyzed using Miles and Huberman’s qualitative data analysis model, which includes data reduction, data display, and conclusion drawing. The results show that teachers’ understanding of STEAM is generally good; however, teachers still experience difficulties in providing contextual learning. Several misconceptions in science were also identified as important findings in this study. These results indicate that comprehensive and intensive mentoring is essential and deserves greater attention.